2014
DOI: 10.1073/pnas.1311945111
|View full text |Cite
|
Sign up to set email alerts
|

Peptides genetically selected for NF-κB activation cooperate with oncogene Ras and model carcinogenic role of inflammation

Abstract: Significance Despite general acceptance of the link between chronic inflammation and cancer, the precise molecular mechanisms underlying the cancer-promoting effects of inflammation remain undefined. Inducible transcription factor NF-κB is the key regulator of inflammation, which is commonly deregulated in cancer cells to become constitutively active. Whether this deregulation contributes to malignant transformation was the main question addressed in this study. We isolated a series of genetic elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…1 and Online methods). A conceptually related approach was recently published that identifies bioactive extracellular peptides 18 .…”
Section: Resultsmentioning
confidence: 99%
“…1 and Online methods). A conceptually related approach was recently published that identifies bioactive extracellular peptides 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Sufficiency of NF-kB activation for overcoming p53's ability to trigger oncogene-induced senescence was shown in our experiments using a set of NF-kB-activating selectable peptides (NASPs) (Natarajan et al 2014). Transduction of NASPs into mouse and rat embryo fibroblasts did not, in itself, alter their growth.…”
Section: Inflammation Can Suppress P53 Functionmentioning
confidence: 63%
“…KO experiments of the NF-jB-pathway revealed that NASPs occur upstream of TNF receptorassociated factor 6. After transduction of NASPs into the fibroblasts of mice and rats resulted in the co-expression of Ras (H-Ras V12) and revealed that rodent fibroblasts mastered the p53-dependent senescence which is mediated by H-Ras V12 and this in turn resulted in a transformed carcinogenic phenotype [117]. These observations underly the different functions of NF-jB and its cooperation with Ras as an oncogene by the attenuation of p53 as well its effects on the inflammatory cascade.…”
Section: Nf-jb Signaling and Crosstalk During Carcinogenesis In Cell mentioning
confidence: 97%
“…For example, the chemotherapeutic efficacy of cisplatin can be enhanced by inhibiting NF-jB in vitro and in vivo [116]. In 2014, an in vitro model of NF-jB driven carcinogenesis was published [117]. The authors used a cell-based phenotypic readout and isolated 12 genetic elements that induced NF-jB activity (NF-jB-activating genetic elements, NASPs) of lentiviral libraries encoding 20 or 50 amino acid-long polypeptides "none of which was previously associated with NF-jB activation, were isolated from libraries of 200 000 peptides derived from 500 human extracellular proteins".…”
Section: In Vitro Nf-jb Cancer Modelmentioning
confidence: 99%
See 1 more Smart Citation